Deciphering the role of multiple generations of annealing twins on texture evolution in cold-rolled high entropy alloys during annealing. (December 2021) - Kaushik, Lalit; Singh, Jaiveer; Kang, Joo-Hee; Ko, Yoon Seok; Kim, Dong-Ik; Suh, Jin-Yoo; Choi, Shi-Hoon
Abstract: The occurrence of multiple generations of annealing twins (MGAT) in low stacking fault energy (SFE) materials leads to significant texture weakening with the evolution of some new prominent texture components. However, the exact correlation between MGAT and texture evolution is a long-standing enigma. In the current research, the presence of MGAT was confirmed by transmission Kikuchi diffraction (TKD) and high resolution electron backscattered diffraction (EBSD) in partially (700 °C/5 min) and fully (700 °C/1 h) recrystallized specimens of equiatomic CoCrFeMnNi high entropy alloy, respectively. Further, the twin clusters in the vicinity of the potential nucleation sites (Brass, Goss and S orientations) were investigated to gain insights on the contribution of MGAT on texture development. The newly developed (φ1 = 90°, Φ=30°, φ2 = 45°) orientation showed its roots originating from 2nd generation twin of the Brass orientation while Cube orientation was evolved from the 1st and 5th generation twins of the S orientation. Graphical abstract: Image, graphical abstract